1996
DOI: 10.1007/bf00228724
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of visual deprivation on vasoactive intestinal polypeptide (VIP)-containing cells in the retinas of juvenile and adult rats

Abstract: Vasoactive intestinal polypeptide (VIP) is a 28 amino acid peptide that has been shown to be present in a distinct subset of retinal amacrine cells (VIP+ cells). Previous work has suggested that the expression of retinal VIP might depend on the lighting conditions prevailing. Reasoning that a careful analysis of the exact conditions of this interaction and its time course might offer clues to the functional role of retinal VIP, we performed a quantitative immunohistochemical analysis of the effects of visual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…VIP‐tdTomato retinas were evaluated for the expression of VIP immunoreactivity. Very weak to weak VIP immunostaining was in small diameter cell bodies in the INL and GCL, and their processes were mainly in strata 1, 3, and 4 of the IPL (Figure b) consistent with previous reports of VIP immunoreactivity in mouse and rat retinas (Lorén et al, ; Eriksen & Larsson, ; Tornqvist et al, ; Terubayashi et al, ; Herbst & Thier, ; Cellerino et al, ). In retinal sections, VIP‐tdTomato fluorescent cell bodies and their processes in both the ON and OFF sublayers of the IPL contained VIP immunoreactivity (Figure ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…VIP‐tdTomato retinas were evaluated for the expression of VIP immunoreactivity. Very weak to weak VIP immunostaining was in small diameter cell bodies in the INL and GCL, and their processes were mainly in strata 1, 3, and 4 of the IPL (Figure b) consistent with previous reports of VIP immunoreactivity in mouse and rat retinas (Lorén et al, ; Eriksen & Larsson, ; Tornqvist et al, ; Terubayashi et al, ; Herbst & Thier, ; Cellerino et al, ). In retinal sections, VIP‐tdTomato fluorescent cell bodies and their processes in both the ON and OFF sublayers of the IPL contained VIP immunoreactivity (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…In rat retina, a double label in situ hybridization and immunohistochemistry study showed co-localization of VIP mRNA and immunoreactivity in amacrine cells (Casini, Molnar, & Brecha, 1994). In mouse and rat retina, other VIP antibodies immunostain amacrine cells with processes that are distributed to multiple strata in the IPL (Lor en, Tornqvist, & Alumets, 1980;Eriksen & Larsson, 1981;Tornqvist et al, 1982;Terubayashi et al, 1983;Herbst & Thier, 1996;Cellerino et al, 2003).…”
Section: Syntaxin 1amentioning
confidence: 99%
“…3). As described in previous studies in rat and mouse retina [5,8,15,34,36], VIP-like immunoreactivity was found in rounded or pear-shaped cell bodies of scattered amacrine cells in the inner nuclear layer and occasionally of amacrine cells displaced in the inner plexiform layer or ganglion cell layer. VIP immunoreactive Fig.…”
Section: Distribution Of Glucagon-related Peptides In the Mouse Retinamentioning
confidence: 61%
“…VIP and PHI also share a common precursor molecule (e.g., [30]) and they were both localized in the mouse eye. Previous studies suggested that VIP expression is controlled by light exposure [8,15,23], as shown by lid suture or dark rearing experiments in primates and rats. Ekman and Tornqvist [7] showed that the retinal glucagon-like immunoreactivity was high in the retinae of birds and cold-blooded animals, but not in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…GABA tonic release, suppressing rod function, is greater in darkness (Boatright et al, 1994); norepinephrine disappears in darkness (Jaffe et al, 1991), and the number of VIPþ cells declines linearly in darkness (Herbst & Thier, 1996). However, as far as we know, none of these neurochemicals has been studied with regard to the rod ERG.…”
Section: Rod Erg Following Four Days In Darknessmentioning
confidence: 95%